2019
DOI: 10.1021/acs.est.9b00473
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Silver Nanoparticles Induce Selective Nanochannels in Thin Film Nanocomposite Polyamide Membranes

Abstract: Thin-film nanocomposite (TFN) membranes have been widely studied over the past decade for their desalination applications. For some cases, the incorporation of nonporous hydrophilic nanofillers has been reported to greatly enhance membrane separation performance, yet the underlying mechanism is poorly understood. The current study systematically investigates TFN membranes incorporated with silver nanoparticles (AgNPs). For the first time, we reveal the formation of nanochannels of approximately 2.5 nm in size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
146
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(151 citation statements)
references
References 54 publications
(100 reference statements)
0
146
0
Order By: Relevance
“…For example, a recent study has observed the presence of non-selective defect channels with a size of B2 nm between embedded silver nanoparticles and polyamide matrix (Fig. 6A), 32 which are detrimental to membrane water-salt selectivity. Although modifying fillers with hydrophobic materials may enhance their miscibility in the polyamide matrix and thus inhibit the formation of the defect channels, 33 the high liquid entry pressure (LEP) in these hydrophobic nanopores would provide additional resistance to water transport.…”
Section: Embedding Nanofillers In the Polyamide Active Layermentioning
confidence: 99%
“…For example, a recent study has observed the presence of non-selective defect channels with a size of B2 nm between embedded silver nanoparticles and polyamide matrix (Fig. 6A), 32 which are detrimental to membrane water-salt selectivity. Although modifying fillers with hydrophobic materials may enhance their miscibility in the polyamide matrix and thus inhibit the formation of the defect channels, 33 the high liquid entry pressure (LEP) in these hydrophobic nanopores would provide additional resistance to water transport.…”
Section: Embedding Nanofillers In the Polyamide Active Layermentioning
confidence: 99%
“…Incorperation of nanoparticles (NPs) (i.e., CuNPs, AgNPs, GONPs etc.) into coating layer results in formation of nanochannels for improving the membrane permeability without compro- mising the membrane selectivity [122]. The future direction of membrane modification technique will be focused on development of new methods that can be implemented in large-scale membrane fabrication through considering the stability and operating costs.…”
Section: Nf Membrane Modificationmentioning
confidence: 99%
“…Thin‐film nanocomposite (TFN) membranes, a new type of nanotechnology‐enhanced membranes, are studied as a promising candidate for desalination purposes. [ 5,6,20–22 ] Many nanoparticles, such as zeolites, [ 6,23–25 ] silica, [ 26,27 ] metal‐organic frameworks−covalent‐organic frameworks (MOFs−COFs), [ 28–30 ] carbon nanotubes, [ 31,32 ] and carbon−graphene oxide quantum dots, [ 33–35 ] have been incorporated into the polyamide matrix of TFN membranes to increase membrane hydrophilicity and provide additional water pathways. [ 36 ] Nevertheless, most of the nanoparticles used are produced in laboratory scale and the yield is relatively low, which is difficult to scale up for commercialization when taking economic viability into account.…”
Section: Introductionmentioning
confidence: 99%